A series of asymmetric zinc (II) phthalocyanines containing fluoro and alkynyl groups: Synthesis and examination of humidity sensing performance by using QCM based sensor - Ahmetali, Erem; Karaoglu, Hande Pekbelgin; Urfa, Yalcin; Altindal, Ahmet; Kocak, Makbule Burkut (ELSEVIER SCIENCE SA, 2020)
In this study, the three novel fluoro substituted asymmetric zinc phthalocyanines substituted with 3-hydroxy-3-methyl-1-butynyl (3), ethynyl (4), and 4-nitrophenylethynyl (5) groups were synthesized and characterized by Fourier-transform infrared spectrophotometer, ultraviolet-visible, proton nuclear magnetic resonance, and matrix-assisted laser desorption/ionization time-of-flight mass spectroscopy. The thickness dependence of relative humidity sensing performance of these compounds using quartz crystal microbalance transducers in a broad operating range of humidity was investigated. Results from this preliminary analysis indicated that responses and the response and recovery times of the 3-5 compound-based relative humidity sensors strongly depended on the thickness of the sensory layer. Experimental studies indicated that the optimized thickness as 450 nm produces a good sensitivity, and the best response and recovery times. The relative humidity sensing results demonstrated that the quartz crystal microbalance sensor coated with peripherally substituted unsymmetrical zinc(II) phthalocyanines bearing nitrophenyl group was the most useful coating for the relative humidity sensing.
Keywords: Asymmetric zinc phthalocyanine; Humidity sensing; QCM Method; NONLINEAR-OPTICAL PROPERTIES; GRAPHENE OXIDE; CARBORANE; DYNAMICS; Materials Science